Pengaruh Media Pembelajaran Daring Terhadap Pengetahuan Belajar Mahasiswa Akuntansi - Sherina Karyanto; Reynard Tandayu; Jessica Febriani; Tan Ming Kuang (Magister Akuntansi FB-UK.Maranatha, 2020)
Instructional media is one of important factors that affect students’ understanding on the learning materials. The main purpose of this study is to examine the impact of instructional media especially e-learning on students’ knowledge in a business education context based on E-learning theory. Data collected from 80 valid respondents at two well-known private universities in Bandung were used to test the research hypothesis using simple regression method. The results indicate that e-learning is perceived as a useful approach for helping accounting students acquire knowledge. This study implies that e-learning may be considered as one approach to deliver knowledge in a business education domain.